Glycoconjugate vaccines: an update. (April 2015) - Vella, Mairi; Pace, David
<x xml:space="preserve">Abstract</x> Introduction: Globally, the three main pathogens causing serious infections are Haemophilus influenzae type b, Streptococcus pneumoniae and Neisseria meningitidis. Over the last 5 years, new vaccines protecting against these bacteria have been developed and introduced in various countries. Areas covered: This review describes the recently licensed glycoconjugates being used to protect against these encapsulated bacteria. Immunogenicity and safety data that led to licensure or licensure expansion of these glycoconjugates are discussed in addition to the resultant impact on the disease burden. Expert opinion: The maintenance of robust immunisation programmes with high uptake rates is important in maintaining low rates of disease. Epidemiological surveillance systems are essential in monitoring any changes in infectious disease trends and in identifying emerging infections such as from non-typeable H. influenzae, pneumococcal serotype replacement disease and changes in the epidemiology of meningococcal serogroups. This is important to guide future vaccine development. Accessibility of these glycoconjugate vaccines in resource poor regions, which bear the highest disease burden from these pathogens, remains challenging largely due to high vaccine pricing. Recent aids from public and private funding, tiered vaccine pricing and the transfer of vaccine technology have helped in introducing these vaccines where they are most needed.